Effect of HIV on mortality among hospitalised patients in South Africa - Dirk J. Lamprecht; Neil Martinson; Ebrahim Variava (AOSIS, 2023)
Background: HIV and AIDS continues to impose substantial healthcare challenges in sub-Saharan Africa, but there are limited local data comparing inpatient outcomes between people with HIV (PLWH) and those uninfected. Objectives: To compare cause-specific mortality among hospitalised adolescents and adults, stratified by HIV-serostatus. Method: A cross-sectional analysis was performed, analysing cause-specific inpatient mortality data and total admissions, from 01 January 2017 to 30 June 2020, at Tshepong Hospital, North West province, South Africa. Results: The overall inpatient mortality rate decreased from 14.5% (95% confidence interval [CI]: 13.4-16.0) in 2017, to 11.3% (95% CI: 10.6-11.9) in 2020; P  0.001. People living with HIV accounted for 53.9% (n = 2342) of inpatient deaths, 22.6% (n = 984) were HIV-seronegative patients and 23.5% (n = 1020) patients with unknown HIV-serostatus. People with HIV died at younger ages (median: 44 years, interquartile range [IQR]: 35.8-54.2) compared to HIV-seronegative inpatients (median: 64.4 years, IQR: 55.5-73.9); P  0.001. Leading causes of death were pneumonia (19.9%, n = 863), then pulmonary and extrapulmonary tuberculosis (15.0%, n = 654). People with HIV who had CD4+ counts 350 cells/mL or viral load ≥ 1000 copies/mL had increased risk of death from tuberculosis compared to virally suppressed patients (adjusted relative risk: 2.10 [95% CI: 1.44-3.04, P  0.009] and 1.56 [95% CI: 1.22-2.00, P  0.001]). Conclusion: Our study, conducted in a regional hospital in South Africa, showed PLWH had higher mortality rates and died at younger ages compared to HIV-seronegative patients.